RELIGIOUS MOBILITY AND IDENTITY IN THE LIVES OF URBAN MUSLIM COMMUNITY IN AUSTRALIA: AN ANATOMY OF RELIGIOUS PRACTICE - Hefni, Wildani; Ahmadi, Rizqa; Purnomo, Maslathif Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
This study aimed to discuss religious mobility in urban Muslim community of Australia by investigating organizational projects and religious practices. In addition, ethnographic fieldwork was conducted, which included extensive interviews and participation in organizational meetings. The results showed that urban Muslim community in Australia contributed significantly to the development of Islamic education, Islamic altruism, and spiritual performance. In this context, social sensitivity was reported by establishing institutions representing Muslim identities, such as Islamic Community of Melbourne Eastern Region (ISOMER) in Melbourne, Islamic Science and Research (ISRA) in Sydney, and Australian Sufi Association (ASA). Furthermore, religious mobility and practices were exemplified as agents of social change through the promotion of community engagement, which served as a manifestation of social solidarity. The three communities engaged in the social sphere were oriented toward spiritual-moral-ethical values to determine social movements in the educational, social, or religious ideology.